The Bible in the Time of the Reformation - Stanko Jambrek (Kairos (English Ed.))
In the first part of the article, the use of the Latin Bible and the Bibles translated in vernacular languages at the time of the Reformation is discussed. In the second part, questions regarding the literal application of the Reformation’s rule, sola Scriptura, are considered, among which questions are included about the canon, authority, sufficiency, perspicuity and understanding of the Bible. In the paper, deliberations of the leading theologians of the Reformation are considered, including each individual question and adopted teachings of particular traditions of the Reformation, as well as the counter-Reformation as recorded in their foundational documents. In the conclusion, it is highlighted that the main message of the Bible is perspicuous even for the illiterate layman; therefore, every person can come to the Bible directly to search for and find truth. The Reformation has reaffirmed that the Bible is the only authority for preaching, theology and daily living, to or from which people should not add or subtract.